Analysis of Alay Language Used By Senior High Students in Masamba – Luwu Utara Regency - Harmita Sari; Suhardi M Anwar; Sumiati Putri Natalia; A. Nurhayati (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The purpose of this study was to describe the use of alay language in the conversations of students of SMA Negeri 2 Masamba, North Luwu Regency. The data source in this study is students of SMA Negeri 2 Masamba, North Luwu Regency and the data was obtained from reading the analysis of previous people's research.The type of research used is descriptive qualitative. Qualitative research is a research procedure that produces descriptive data in the form of written or oral words from people and observed behaviors.Data collection techniques consist of: observation, recording, tapping techniques, and documentation. The results of research on the use of contemporary language or alay language used by the students of SMA Negeri 2 Masamba North Luwu Regency in the form of phoneme additions, phoneme removal that occurred at the beginning of the word, the middle of the word, and the end of the word, the use of new terms is also the use of alay language used by students of SMA Negeri 2 Masamba North Luwu Regency.In addition, another form of the use of alay language used by students found by researchers is the replacement of haruf in the word.